2017
DOI: 10.1039/c7tx00043j
|View full text |Cite
|
Sign up to set email alerts
|

Toxic mechanisms of microcystins in mammals

Abstract: Microcystins, such as microcystin-leucine arginine (MC-LR), are some of the most toxic and prevalent cyanotoxins produced by cyanobacteria in freshwater and saltwater algal blooms worldwide. Acute and chronic exposures to microcystins are primarily known to cause hepatotoxicity; cellular damage and genotoxicity within mammalian livers. However, studies indicate that similar damage may occur in other mammalian organs and tissues, such as the kidney, heart, reproductive systems, and lungs - particularly followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(69 citation statements)
references
References 97 publications
0
61
0
1
Order By: Relevance
“…Depending on the MC congener, the dose, and the duration of exposure, MCs cause necrotic, apoptotic, or cell-proliferative changes [90,91]. Due to the high abundance of OATP1B1 and 1B3 in parenchymal hepatocytes, the high metabolic activity, and detoxifying function, toxic effects often manifest in the liver, even though the first site of action upon water-borne contaminants is probably mucosal epithelia of the GIT (Table 2).…”
Section: Microcystin Effectsmentioning
confidence: 99%
“…Depending on the MC congener, the dose, and the duration of exposure, MCs cause necrotic, apoptotic, or cell-proliferative changes [90,91]. Due to the high abundance of OATP1B1 and 1B3 in parenchymal hepatocytes, the high metabolic activity, and detoxifying function, toxic effects often manifest in the liver, even though the first site of action upon water-borne contaminants is probably mucosal epithelia of the GIT (Table 2).…”
Section: Microcystin Effectsmentioning
confidence: 99%
“…Large MC doses lead to acute liver failure [7,9], but prolonged exposure to low levels of MCs may be more prevalent and pernicious. The effects of such exposure in humans are not well understood and are generally extrapolated from animal models [24][25][26][27][28]. Animal studies have found biomarkers of MC exposure in mouse serum [29] and rat urine [30] after intraperitoneal injection.…”
Section: Introductionmentioning
confidence: 99%
“…The gene cluster of the MC biosynthesis pathway in Microcystis consists of ten genes (mcyA-J, approximately 55 kb in length) [12,13]. With the establishment of a genetic basis of MCs biosynthesis, various molecular approaches have been subsequently developed for detecting and quantifying the potential of MC-producing cyanobacteria [14,15]. While the biosynthesis, identification, detection, and toxicity of MCs have been well understood [16], the biological and ecological functions of these metabolites still remain a subject of debate [17].…”
Section: Introductionmentioning
confidence: 99%